Financiamento público da pesquisa em recursos hídricos no Brasil: O fundo setorial CT-Hidro - Gesmar Rosa dos Santos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– The aim of this study is to analyze the characteristics and dynamic performance of the Water Resources Sector Fund of the Ministry of Science and Technology (CT-Hidro/MCT) as a result of the partnership between the Ipea and the Brazil's MCT. Quantitative and qualitative aspects, as well as challenges of managing water resources and the demands generated by them to the research, development and technological innovation are addressed. The organizational system and emerging issues are also addressed starting from the technicians and managers point of view on the CT-Hidro. It appears that the CT-Hidro has played an important role in financing research and in response to the challenges posed to it, and has achieved goals and regional percentage distribution tothe lines supported. On the other hand, we emphasize a low networks integration, a low compliance of companies and a consequent low focus on technological innovation.
Keywords: O31; O32; E; O38; 330; technological innovation; water resources; public funding